Closure of Petersen’s defect in gastrectomy for gastric cancer: an interrupted time series analysis from a high-volume institution in China - Pan, Tao (Langenbecks Arch Surg, 2020)
PURPOSE: Petersen’s hernia (PH) is a serious complication after gastrectomy for gastric cancer. The aim of this study was to investigate whether closure of Petersen’s defect (PD) can decrease the rates of PH and suspected Petersen’s hernia (SPH). METHODS: Patients who underwent gastrectomy with PD were enrolled. From January 2014 to January 2017, we performed gastrectomy without PD closure (non-closure group). From February 2017 to June 2018, we closed PDs during gastrectomy (closure group). The rates of PH and SPH were compared between the two groups. The last follow-up was updated in August 2020. RESULTS: Among a total of 1213 patients, 12 patients (1.0%) developed PH, and 23 patients (1.9%) developed SPH. The rate of PH in the closure group was significantly lower than that in the non-closure group (1/385, 0.3% versus 11/828, 1.3%, p = 0.042, log-rank test). The rate of SPH in the closure group was significantly lower than that in the non-closure group (1/385, 0.3% versus 22/828, 2.7%, p = 0.008, log-rank test). Non-closure of PD was a risk factor for PH and SPH (odds ratio (OR) 7.72, 95% CI 1.84–32.35, p = 0.006). CONCLUSIONS: PD closure is recommended after gastrectomy for gastric cancer, as the rates of PH and SPH were significantly decreased.